Registers as the basis for data collection and evidence building - A. V. Ivanov (Реальная клиническая практика: данные и доказательства)
The development of medical science requires a constant increase in the effectiveness and safety of treatment. Collection of real-world data (RWD) is one way of solving these problems. Clinical registries are one of the most important parts of this process. Clinical registries allow collecting data on the use of medical technologies and monitoring the results of therapy in real clinical practice. The introduction of patient registers and the collection of RWD data into widespread medical practice can help to optimize costs in the treatment of high-cost diseases and to better plan the budget.